2016
DOI: 10.5114/aoms.2016.59260
|View full text |Cite
|
Sign up to set email alerts
|

Impact of septal flash and left ventricle contractile reserve on positive remodeling during 1 year cardiac resynchronization therapy: the multicenter ViaCRT study

Abstract: IntroductionCardiac resynchronization therapy (CRT) has been shown to improve outcomes in patients with systolic heart failure (HFREF). However, the relatively high non-responder rate results in a need for more precise qualification for CRT. The ViaCRT study was designed to determine the role of contractile reserve and dyssynchrony parameters in predicting CRT response. The purpose of this analysis was to determine the effect of baseline septal flash and contractile reserve (CR) on clinical and echocardiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…While pharmacological therapy has signifi- 2 Arch Med Sci cantly improved clinical outcome in patients with HF and reduced ejection fraction (HFrEF), a subgroup still remains symptomatic and with poor quality of life [2]. This limited clinical improvement urged researchers and clinicians to identify other therapeutic potentials that could alleviate symptoms in such patients [3], particularly those requiring cardiac resynchronisation therapy (CRT) [4]. Despite being considered the best treatment for symptomatic HF patients on full medical therapy, one third of subjects receiving CRT do not respond [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…While pharmacological therapy has signifi- 2 Arch Med Sci cantly improved clinical outcome in patients with HF and reduced ejection fraction (HFrEF), a subgroup still remains symptomatic and with poor quality of life [2]. This limited clinical improvement urged researchers and clinicians to identify other therapeutic potentials that could alleviate symptoms in such patients [3], particularly those requiring cardiac resynchronisation therapy (CRT) [4]. Despite being considered the best treatment for symptomatic HF patients on full medical therapy, one third of subjects receiving CRT do not respond [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Third, 3 in 4 patients in our study had vegetations that could be visualised using echocardiography [12,19,22]. Echocardiography is an established method for both qualifying patients for CRT therapy and assessing its response [23,24]. Our findings show that echocardiography also plays a key role in diagnosing CRT-related CDRIE, particularly in the absence of positive blood cultures.…”
Section: 5%mentioning
confidence: 66%
“…Our search yielded 543 studies and after detailed screening and review, a total of nine studies were included [ Figure 2 ]. [ 13 14 15 18 19 20 21 22 23 ]…”
Section: R Esultsmentioning
confidence: 99%
“…All studies used either two-dimensional (2D or 3D) TTE to assess for the presence of septal flash. [ 13 14 15 18 19 20 21 22 ] One study used a combination of 2D TTE and CMR. [ 23 ] Details results extracted from each of the included studies is shown in Table 3 .…”
Section: R Esultsmentioning
confidence: 99%
See 1 more Smart Citation